Redo Laparoscopic Pyeloplasty in Children: Results from a Multicentric Series - Pedro-Jose Lopez; Alejandro Calvillo-Ramirez; Ahmet Sancaktutar; Francisca Yankovic; Juan Manuel Moldes; Juan Pablo Corbetta; Luis Garcia-Aparicio; Luis H. Braga; Francisco Reed (International Brazilian Journal of Urology)
ABSTRACT Purpose: To describe the experience of five training centers with redo laparoscopic pyeloplasty (RLP) in children with restenosis of the uteropelvic junction (UPJ), assessing whether this approach increased or not postoperative complications or surgery failure. Materials and Methods: A retrospective, descriptive study was conducted, including 19 patients who underwent transperitoneal RLP at five independent training centers across 4 different countries between January 2009 and December 2017. All patients had previously undergone Anderson-Hynes dismembered pyeloplasty. Primary outcomes included postoperative complication rates and redo surgery failure. Results: There were 19 RLP out of 744 primary laparoscopic pyeloplasties. Median operative time was 150 minutes (interquartile range [IQR] 126.2-180), extended by 19 minutes when colon mobilization was performed. No cases required conversion to open surgery. A median postoperative analgesic requirement and length of stay of 5 and 4 days, respectively, were recorded. No major complications were reported except a single instance of temporary UPJ stenosis, which was managed with a nephrostomy tube and did not require further surgery. After a median follow-up of 17 months, we achieved a 100% success rate. A significant reduction in renal pelvis dilation was noted, with the median anteroposterior diameter (APD) decreasing from 43 mm preoperatively to 17 mm postoperatively (IQR 10–22). Conclusions: Our findings suggest that RLP remains a feasible approach in the management of restenosis of the UPJ even in such different healthcare settings, providing success rates as high as those described in primary pyeloplasty while maintaining a safety profile.